Effect of copper on diesel degradation in Pseudomonas extremaustralis - Colonnella, Maria Antonela; Lizarraga, Leonardo; Rossi, Leticia; Díaz Peña, Rocío; Egoburo, Diego Ezequiel; López, Nancy Irene; Raiger Iustman, Laura Judith (Extremophiles)
Environments co-contaminated with heavy metals and hydrocarbons have become an important problem worldwide, especially due to the effect of metals on hydrocarbon degrading microorganisms. Pseudomonas extremaustralis, a bacterium isolated from a pristine pond in Antarctica, showed high capabilities to cope with environmental stress and a very versatile metabolism that includes alkane degradation under microaerobic conditions. In this work, we analyzed P. extremaustralis? capability to resist high copper concentrations and the effect of copper presence in diesel biodegradation. We observed that P. extremaustralis resisted up to 4 mM CuSO 4 in a rich medium such as LB. This copper resistance is sustained by the presence of the cus and cop operons together with other efflux systems and porins located in a single region in P. extremaustralis genome. When copper was present, diesel degradation was negatively affected, even though copper enhanced bacterial attachment to hydrocarbons. However, when a small amount of glucose (0.05% w/v) was added, the presence of CuSO 4 enhanced alkane degradation. In addition, atomic force microscopy analysis showed that the presence of glucose decreased the negative effects produced by copper and diesel on the cell envelopes. Fil: Colonnella, Maria Antonela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Centro de Investigaciones en Bionanociencias "Elizabeth Jares Erijman"; Argentina Fil: Lizarraga, Leonardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Centro de Investigaciones en Bionanociencias "Elizabeth Jares Erijman"; Argentina Fil: Rossi, Leticia. Universidad de Buenos Aires; Argentina Fil: Díaz Peña, Rocío. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales. Universidad de Buenos ...